Order of the International Ban and Albania’s Agreements with Other Countries - Hasani, Nikolin (European Journal of Multidisciplinary Studies, 2016)
Higher stage of cooperation in criminal matters between European states is undisputed the adoption of the International Order of Prohibition (UEN) which was materialized by means of Decision Framework Constitution Nr.584 , dated June 13, 2002. This decision was endorsed by the EU Council and published in its official bulletin on June 18, 2002. Among the EU member states this order replaces classical Extradition procedure, except when some member states have declared that they will continue to implement the conventions of Extradition. From this moment the extradition procedures applied within the EU, are without legal force. The aim of this paper is to present a brief analyse of Albania’s agreements with other countries, pointing out specific aims of them, specific conditions of implementations according the specifical need for judicial cooperation between Albania and each of these countries